Clinical characteristics and comparative analysis of PD-1/PD-L1 inhibitor-induced pituitary dysfunction versus other pituitary disorders - Yan Xiao; Deyue Jiang; Shengjie Wang; Lei Fu; Lingtong Ye; Erhan Zheng; Zhaohui Lv; Yiming Mu; Wenwen Gong; Qinghua Guo (Scientific Reports)
Abstract This study aims to investigate the clinical characteristics of programmed cell death protein-1 (PD-1) or programmed cell death ligand-1 (PD-L1) inhibitors-induced pituitary injury (pituitary-irAE) by comparing with other pituitary diseases. We retrospectively reviewed clinical records of patients who were admitted for pituitary-irAE, idiopathic isolated ACTH deficiency (IIAD), and lymphocytic hypophysitis (LYH) from January 2015 to June 2024. Among 3689 patients treated with PD-1/PD-L1 inhibitors, 0.596% patients developed pituitary-irAE. The mean age of onset was 59.41 ± 10.69 years, with 13 patients (59.09%) being male. The median duration from symptom onset to confirmed diagnosis was 5.50 (2.00, 9.25) months. The clinical symptoms were similar between pituitary-irAE and IIAD, which mainly manifested as fatigue and appetite loss. Polydipsia/polyuria and amenorrhea/menstrual disorders were mainly found in patients with LYH. Central adrenal insufficiency was observed in all patients with pituitary-irAE, with cortisol concentrations typically falling below the detectable limit. Pituitary MRI appeared normal in 52.63% patients with pituitary-irAE. Furthermore, some patients with pituitary-irAE exhibited partial or complete functional recovery of the pituitary gland after hormone replacement therapy. The clinical manifestations observed in patients with pituitary-irAE are analogous to those seen in individuals with IIAD, yet they differ from the presentations of LYH.